Performance of 2014 NICE defibrillator implantation guidelines in heart failure risk stratification. Issue 10 (8th February 2016) - Cubbon, Richard M; Witte, Klaus K; Kearney, Lorraine C; Gierula, John; Byrom, Rowenna; Paton, Maria; Sengupta, Anshuman; Patel, Peysh A; MN Walker, Andrew; Cairns, David A; Rajwani, Adil; Hall, Alistair S; et al.
Abstract : Objective: Define the real-world performance of recently updated National Institute for Health and Care Excellence guidelines (TA314) on implantable cardioverter-defibrillator (ICD) use in people with chronic heart failure. Methods: Multicentre prospective cohort study of 1026 patients with stable chronic heart failure, associated with left ventricular ejection fraction (LVEF) ≤45% recruited in cardiology outpatient departments of four UK hospitals. We assessed the capacity of TA314 to identify patients at increased risk of sudden cardiac death (SCD) or appropriate ICD shock. Results: The overall risk of SCD or appropriate ICD shock was 2.1 events per 100 patient-years (95% CI 1.7 to 2.6). Patients meeting TA314 ICD criteria (31.1%) were 2.5-fold (95% CI 1.6 to 3.9) more likely to suffer SCD or appropriate ICD shock; they were also 1.5-fold (95% CI 1.1 to 2.2) more likely to die from non-cardiovascular causes and 1.6-fold (95% CI 1.1 to 2.3) more likely to die from progressive heart failure. Patients with diabetes not meeting TA314 criteria experienced comparable absolute risk of SCD or appropriate ICD shock to patients without diabetes who met TA314 criteria. Patients with ischaemic cardiomyopathy not meeting TA314 criteria experienced comparable absolute risk of SCD or appropriate ICD shock to patients with non-ischaemic cardiomyopathy who met TA314 criteria. Conclusions: TA314 can identify patients with reduced LVEF who are at increased relative risk of sudden death. Clinicians should also consider clinical context and the absolute risk of SCD when advising patients about the potential risks and benefits of ICD therapy.